The Clinical Effect of Digital Dorsal Fascial Island Flap Combined With Crossfinger Flap for Repairing Distal Degloving Injury and Sensory Reconstruction - Hao, Ruizheng; Huo, Yongxin; Wang, Hui; Liu, Wei (Frontiers in Surgery, 2022)
Background. To explore the clinical effect of digital dorsal fascial island flap combined with cross-finger flap to repair distal degloving injury and sensory reconstruction. Methods. A total of 19 patients with distal fingertip degloving injuries treated with digital dorsal fascial island flap combined with cross-finger flap in our hospital from April 2018 to August 2020 were retrospectively included. Semmes–Weinstein (SW) monofilament and static two-point discrimination (S-2PD) tests, active range-of-motion (ROM) of the fingers, cold intolerance, visual analog scale (VAS) score patient complications and patient satisfaction were evaluated. Results. 5 cases with postoperative flap blisters were treated at time of dressing changes up to successful scab formation. 3 cases with postoperative arterial crisis of finger arterial dorsal branch vessel were relieved after suture removal and tension reduction. All other skin flaps and skin grafts survived. 19 patients received follow-up between 3 and 26 months (average 14.6 months).The active ROM of metacarpophalangeal (MCP) and interphalangeal (IP) joints of the injured fingers were satisfactory. Conclusion. The digital dorsal fascial island flap combined with the cross-finger flap for repairing the distal degloving injury of the distal segment of the finger is a good surgical method, which is simple and easy to operate, can repair a large area of soft tissue defect, and obtain a satisfactory effect.